DEVELOPMENT OF INSTRUMENT TO ASSESS BASIC NEEDS OF THE FAMILY FOR NURSING CARE IN THE GARUT REGENCY OF WEST JAVA, INDONESIA - Dian Roslan Hidayat; M. KesLely Wijayanti, (The Malaysian Journal of Nursing (MJN), 2015)
The implementation of family nursing care by nurses in the Garut Regency of West Java of Indonesia posses a problem. The is due to the lack of documentation of family nursing process. According to the report of Cilacap Inpatient Health Center (2010) the average assessment at this stage is only 23.81%. This study aims to provide a new option for nurses to conduct a study to assess the basic needs of the family. This study used the method of investigation and development. Researchers prepare and developed assessment instruments and subsequently tested with the nurses to determine the suitability. The results of the study revealed that based on research development that the basic needs of the family consist of biological needs, economic, spiritual, social, and psychological. Therefore it can be concluded that based on the results of research it can be stated that almost all of the respondents (76.5%) declared suitability of nursing care but only small proportion of respondents (23.5%) said that family nursing assessment is not suitable, based on the basic needs of the family.